3D-printed moulds facilitate making an anatomically matched cement spacer for reconstruction long bone defection after resection of tumors of humerous - Zhao, Haltao; Sigdel, Arun; Hou, Xizhi; Zhang, Ting; Zhang, Guochuan; Sun, Tao (Nepalese Journal of Cancer, 2018)
Background: A nail and cement spacer is one of the option for the reconstruction of the proximal humerus after tumor resection among prosthesis unaffordable patients. However, making the cement spacer anatomically match its replacement remains challenging.Presentation of case: A 12-year-old boy was diagnosed with osteosarcoma in the right proximal humerus by core needle biopsy. After preoperative neo-adjuvant chemotherapy, a wide resection was performed, and the defect was reconstructed with an anatomically matched cement spacer. The cement spacer was fabricated using 3D-printed moulds, which were made according to the mirror image of the left humerus based on CT data. The post-operative course was uneventful, and at the 12-month follow-up, the patient is able to move with only some restriction in abduction and upward lift. The MSTD score was 21.Conclusion: Fabrication of an anatomically matched cement spacer using 3D-printed moulds is a simple, inexpensive, and reproducible procedure for reconstruction complex bone defect.